Meta-Analyze of the Scientific Papers on the Effects of the Preparation Period on the Situational Motor Skills of the Cadet Football Players - Ivan Vasiljevic (Journal of Anthropology of Sport and Physical Education)
The main goal of the research was to make one meta-analyze of original scientific papers, mostly published in the Sport Mont Journal, who dealt with the identification of the level of quantitative changes in situational motor skills at cadet football players under the influence of the programmed training process in the preparation period. Three tests were used for estimation of each situational motor ability. In the field of comparative statistics, for determining the differences in variables used to estimate situational motor abilities at the beginning (starting state) and at the end (final state) of the training program during the preparation period, a discriminating parametric procedure t-test was used for large dependent samples. Based on the numerical values of t-test, in all the aforementioned published papers, it was the concluded that statistically significant positive quantitative changes occurred in situational motor skills during the preparation period of cadet football players. Such a training program during the preparation period proved to be very effective in raising the level of situational motor skills in cadet football players. This meta-analyze shows that the obtained results can be focused on innovative plans and programs in the preparation period as well as on adapting the same to the needs of the appropriate population.